EFFECTS OF GRADED LEVELS OF FERMENTED SUNFLOWER SEED MEAL ON GROWTH PERFORMANCE AND NUTRIENT DIGESTIBILITY OF GROWING RABBITS - Yusuf, A. A.; Nyako, N. D.; Yahya, M.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
An eight weeks feeding trial was conducted on the effects of graded level of fermented sunflower seed meal on the performance and nutrient digestibility of growing rabbits using forty-five Rabbits cross bred (New Zealand X Dutch) ranging from five to six weeks of age with average weight of 650.34 g. The rabbits were randomly allotted to five dietary treatments of nine rabbits each replicated 3 times with 3 rabbits per replicate in a Completely Randomized Design, each treatment diet contains 0, 5, 10, 15 and 20% FSSM in diet 1(control), 2,3,4 and 5 respectively. The parameters measured include proximate composition of fermented sunflower seed meal, feed intake, weight gain and feed conversion ratio. Others are nutrient digestibility such as dry mater (DM), Crude protein (CP), Crude Fiber (CF), Ether Extract(EE), Ash and Nitrogen Free Extract (NFE). The results for Growth Performance Parameters indicated that There were significant (P<0.05) differences among the treatment groups in total body weight and daily feed intake which ranges between 553.95 to 614.70 g and 45.02 to 52.16g respectively. However, the results for nutrient digestibility showed significant (P<0.05) difference among treatment groups for crude protein, crude fiber, ether extract, ash and nitrogen free extract. Conclusively, inclusion of 20% FSSM in Rabbits diet gave a better result on growth performance and nutrient digestibility without any adverse effect and can be adopted by Rabbit farmers for better performance.